Показатели фагоцитоза и экспрессии дифференцировочных маркеров СD T-лимфоцитов у больных с артериальной гипотонией в отдаленном периоде закрытой черепно-мозговой травмы, с церебральным арахноидитом и вегетативной дисфункцией - Климова, Елена Михайловна; Литовченко, Т. А.; Зинченко, Елена Константиновна; Шапоренко, С. В. (Харківський національний медичний університет, 2006)
Изучена фагоцитирующая активность гранулоцитарных нейтрофилов и экспрессия дифференцировочных рецепторов CD Т-лимфоцитов у больных, страдающих артериальной гипотонией в отдаленном периоде закрытой черепно-мозговой травмы, при церебральной арахноидите и вегетативной дисфункции, а также сопоставлены эти изменения с тяжестью течения заболевания.

Saving dynamic homeostasis in the organism is realized by nervous, immune and endocrine systems, witch represent a single hole and interact on principle mutual regulation as in normal conditions as under different patologic influences. The aim of our research is studying of ingestion rate of granulocytic neutrophils and expresion of differentiation receptors CD T-lymphocytes of group of patients suffering arterial hypotonia at the remote period of closed craniocerebral injury, in the presence of cerebral arachnoiditis and vegetative dysfunction and also confrontation of these changes with the difficulty of clinical course.
Indexes of phagocytosis in expresion of differentiation markers CD T-lymphocytes of the patients suffering arterial hypotonia at the remote period of closed cranio-cerebral injury, in presence of cerebral arachnoiditis and vegetative disfunction
Keywords: гомеостаз; гематоэнцефалический барьер; артериальная гипотония; гранулоцитарные нейтрофилы; homeostasis; hemato-encephalitic barrier; arterial hypotonia; granulocytic neutrophil